THE DESIGN OF MOSQUES AS COMMUNITY DEVELOPMENT CENTERS FROM THE PERSPECTIVE OF THE SUNNA AND WRIGHT’S ORGANIC ARCHITECTURE - Nangkula Utaberta, Mohamad Tajuddin Mohamad Rasdi (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2010)
The main purpose of this paper is to present an alternative approach to mosque design with particular reference to the context of Malaysia and the Malay World or the Nusantara. The paper contains four main parts. The first part examines the problem of mosque architectural interpretation from the perspective of Western architectural historiography. The main problems highlighted are those which pertain to the idea of ‘architecture’, ‘religious architecture’, relevance of the body of knowledge known as the ‘Hadith’ and lastly the specific historical-political agenda of some traditional mosques. The second part of the paper expounds briefly a reinterpretation of the hadith in arguing that the mosque approaches more as a community development complex than that as a mere house of rituals. The third part of the paper examines Wright’s Organic Architecture with specific reference to the design of the Unity Church and a few other buildings as containing some important lessons of mosque designs from the perspective of the Sunnah. The final part of the paper uses the principles discussed to criticize the Putra Mosque and the Masjid Negara.